Joint effects of weather variables on rice yield - AGRAWAL, RANJANA; JAIN, R. C.; JHA, M. P. (MAUSAM, 1983)
An attempt has been made to study the joint effect of climatic variables on rice yield at different stages of crop growth. Beneficial effects of above average maximum temperature on yield increased with rise in humidity during active vegetative phase while detrimental effects decreased in other phase of crop growth. The rise in humidity had small beneficial effects in general throughout the crop season. The effects increased with increase in temperature. Rise in temperature associated with high rainfall had beneficial effects during growth phase of the crop.